Caracterização e desenvolvimento de uma nanoformulação larvicida incorporada ao óleo essencial de Salvia officinalis L. - PEREIRA, Ana Patrícia Matos (2022)
This study aims to evaluate the chemical profile and biotechnological larvicidal potential of (O/W) nanoemulsion incorporated with the essential oil of Salvia officinalis L. The plant material was obtained in São Luís (MA) between January and May. 2021. The Phytochemical profile was performed according to Matos. The essential oil was extracted by hydrodistillation at 100 °C for 3 h. The physical chemical parameters were determined and the chemical characterization obtained by GC-MS. The O/W nanoemulsion was formulated by the low-energy phase inversion method, being subjected to thermodynamic stability tests and characterization of droplet size and polydispersity index (PDI). The quantification of phenolics was performed by the Folin-Ciocalteu method. Antioxidant activity performed by the spectrophotometric method of scavenging hydroxyl radicals from salicylic acid. For larvicidal activity, Aedes aegypti larvae were subjected to EO solutions and nanoemulsions in concentrations (10-100 mg L-1), larval mortality was evaluated and the LC50 was determined by the Probit method. The major secondary metabolites of EO were: eucalyptol with 65.14%, camphor (30.63%) and α-Terpineol (1.53%). The EO was non-toxic, with LC50 <1000 mg L-1. The formulations were droplets as nanoemulsions with volume <200 nm. The PDI was <0.200, indicating a narrow size distribution. The total phenolic content was 8.53 mg EAT g-1 and 12.12 mg EAT g-1. The antioxidant activity exhibited EC50 of 136.29 mg L-1 and 51.59 mg L-1. The nanoemulsion with larvicidal potential showed an LC50 of 71.17 mg L-1. The studied EO nanoemulsion showed active larvicidal activity, being encouraged as a new alternative for the control and combat of Aedes aegypti cases.